2022
DOI: 10.1007/s00603-022-02867-y
|View full text |Cite
|
Sign up to set email alerts
|

Real-Time Measurement of Mechanical Behavior of Granite During Heating–Cooling Cycle: A Mineralogical Perspective

Abstract: Changes in mechanical properties of rocks at high temperatures are significant to various scientific and engineering problems, such as efficient exploration in enhanced geothermal systems (EGS) and rock mass stability in radioactive waste disposal. However, a comprehensive understanding of changes in rock mechanical behaviors at high temperatures and corresponding mechanisms, especially granites, remains unclear, which calls for the examination of micromechanical properties of the constituent minerals. This wo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(9 citation statements)
references
References 63 publications
2
7
0
Order By: Relevance
“…11b) accompanied by clear permeability enhancement. This is consistent with previous observations (Li et al 2021;Mo et al 2022;Zhao et al 2021). The transition from velocity-strengthening to velocity-weakening response is dominated by the response of strong and brittle minerals (i.e., quartz and feldspar) on the fracture surface.…”
Section: Microstructural Characterizationsupporting
confidence: 92%
“…11b) accompanied by clear permeability enhancement. This is consistent with previous observations (Li et al 2021;Mo et al 2022;Zhao et al 2021). The transition from velocity-strengthening to velocity-weakening response is dominated by the response of strong and brittle minerals (i.e., quartz and feldspar) on the fracture surface.…”
Section: Microstructural Characterizationsupporting
confidence: 92%
“…Granite samples were an outcrop mined from the Gonghe Basin located in Qinghai Province, China, where a pilot EGS site was established. The mineral composition and the fundamental physical and mechanical properties from our previous research (Mo et al., 2022) are presented in Table 2.…”
Section: Methodsmentioning
confidence: 99%
“…The Mineral Compositions and Fundamental Physico-Mechanical Properties of Granite Samples (Mo et al, 2022)…”
Section: Tablementioning
confidence: 99%
“…Kothari et al 13 ties of the quartz crystal; instead, the crystal structure of minerals will have an increasing influence on the mechanical properties and lattice defect of mineral crystals. 14 The fundamental defects in both crystalline and alpha SiO 2 have been studied intensely for decades. The oxygen vacancy is important and has also been formed to the fundamental positive charge trap in bulk.…”
Section: Introductionmentioning
confidence: 99%
“…Kothari et al also indicated that vacancy defects are the main factor affecting the thermal conductivity of carbon nanotubes CNTs. With the particle size of quartz minerals decreasing below microns, the properties of macroscopic cleavage cannot accurately characterize the mechanical properties of the quartz crystal; instead, the crystal structure of minerals will have an increasing influence on the mechanical properties and lattice defect of mineral crystals . The fundamental defects in both crystalline and alpha SiO 2 have been studied intensely for decades.…”
Section: Introductionmentioning
confidence: 99%